Pola Komunikasi Orang Tua Terhadap Perkembangan Anak - Firyal Labibah Luthfiyah; Nina Yuliana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
In this sense, "communication patterns" refers to the format or method of communication between parents and children that is based on communication theories and creates reciprocity to support methodical and logical thought. Physical, linguistic, emotional, and cognitive changes occur during a child's growth from birth to the early years of maturity. Children in elementary school are given gadgets by their parents for a specific purpose, but when a child actively uses a gadget, their communication patterns are given extra consideration. This study intends to understand how parents communicate with their children in order to help them form their character, investigate the connection between parental communication styles and the language development of children between the ages of four and six, and investigate the impact of family interpersonal communication styles on the character development of children. The PGRI Sukabela Pos Complex in Kasemen District, Serang City, was used as the research place while deciding on the qualitative research methodology. According to these results, communication between parents and kids has an impact on kids' language development at the crucial 4-6 year old age range. During this time, parents' rich and constructive communication exchanges with their kids are crucial to the language development of the kids. Youngsters who talk to their parents frequently, intently, and encouragingly typically develop their language skills better.